LINKS IN JOURNEY OF IDEA TO PRODUCT IN CREATIVE WRITING - Sarif Syamsu Rizal (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2011)
This study aims to discuss â€œLinks in Journey of Idea to Productin Creative Writingâ€. The study explores influencing elements in creative writing process up to be a literary work as a masterpiece. Methods of the study consist of qualitative design in explaining discourse, library research in collecting data, and causal approach in answering the problem statement that is how and why creative writing can promote local culture. Units of analysis cover the factors in the elements building the literary work as the product of creative writing conducted by author. Writing is a form of personal freedom. It frees the author from the mass identity he or she seesall around. In the end, he or she will write not to be outlaw hero of some under culture but mainly to save him or herself, to survive as individuals. Furthermore, creative writing is anything in which the purpose is to express thoughts, feelings and emotions rather than to simply convey information.Keywords: journey, creative writing, literary work, author